2004
DOI: 10.1021/jf035127x
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Extraction of β-d-Glucans from Saccharomyces cerevisiae Cell Wall and Study of Their Adsorptive Properties toward Zearalenone

Abstract: The isolated cell wall of Saccharomyces cerevisiae has some capacity to adsorb zearalenone (affinity near 30%) and reduce the bioavailability of toxins in the digestive tract. The adsorption process was quantified in vitro, and the data obtained when plotted with Hill's equation indicated a cooperative process. The model showed that the adsorption capacity was related to the yeast cell wall composition. This work focused on the role of various beta-d-glucan types in the efficacy of zearalenone adsorption by ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 24 publications
4
75
0
Order By: Relevance
“…The mechanism of binding by β-Dglucans has been investigated by Yiannikouris and co-workers and has been discussed in several publications, e.g. (Yiannikouris et al 2004a;Yiannikouris et al 2006;Yiannikouris et al 2004b;Yiannikouris et al 2004c). It was shown that it is important to differentiate between the adsorption affinity of whole yeast cell wall and processed cell wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of binding by β-Dglucans has been investigated by Yiannikouris and co-workers and has been discussed in several publications, e.g. (Yiannikouris et al 2004a;Yiannikouris et al 2006;Yiannikouris et al 2004b;Yiannikouris et al 2004c). It was shown that it is important to differentiate between the adsorption affinity of whole yeast cell wall and processed cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…A further factor influencing the binding ability is the presence of chitin which stiffens the cell wall structure and restricts access of e.g. ZON to the binding sites of β-D-glucans (Yiannikouris et al 2004c). Therefore, the preparation of the cell wall material prior to its application as a mycotoxin binder is of major importance and greatly influences the adsorption ability of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Protective effect against aflatoxins produced by yeasts was confirmed in rats. However, when yeast cells were inactivated by heat, they were inefficient [80] but when glucomannanes extracted from the cell wall of yeasts were used, there was an increase in the efficiency of the bond with AFB 1 , OTA and T-2 toxin [81][82][83][84], individually or in combination [75,79,85,86]. The addition of SC in the diet reduced AFB 1 toxic effects in chickens [72,87].…”
Section: Decontamination Of Aflatoxins By Yeastsmentioning
confidence: 99%
“…The second major yeast cell wall polysaccharide, (1→3)(1→6)--D-glucan, might also contribute to yeast cell wall biological properties (section 5 of this chapter), but its major role in animal nutrition is its ability to bind mycotoxins and detoxify animal feed. The (1→3)(1→6)--D-glucan is a part of the cell wall's "triple helix tridimensional structure, with spring-like mechanical properties, responsible for yeast cell wall strength and ability to absorb toxins" (Yannikouris et al, 2004) (see section 2, this chapter). Toxins occurring in plant-derived animal feed belong to one of two groups.…”
Section: Baker's Yeast Cell Wall -D-glucan/ -Mannoprotein Complexmentioning
confidence: 99%